Gastric ultrasound as a preoperative bedside test for residual gastric contents volume in children. Issue 12 (20th August 2016) - Schmitz, Achim; Schmidt, Alexander R.; Buehler, Philipp K.; Schraner, Thomas; Frühauf, Melanie; Weiss, Markus; Klaghofer, Richard; Kellenberger, Christian J.
Summary: Background: Emergency situations and conditions with impaired gastric emptying enhance the risk of perioperative pulmonary aspiration due to increased residual gastric contents volume (GCV). Gastric ultrasonographic (US) measurement of the gastric antral cross‐sectional area (CSA) has been proposed to estimate preanesthetic GCV. However, only few healthy children and fasted pediatric patients have been investigated so far, predicting GCV with considerable imprecision. This study aimed to compare GCV assessed by US in different patient positions for measuring CSA, using magnetic resonance imaging (MRI) as reference, and to evaluate its potential as diagnostic test. Methods: Healthy volunteer children were examined in a crossover design on 2 days. After baseline examination, they received a light breakfast, followed by 7 ml·kg −1 clear fluid after 2 or 4 h. Gastric emptying was examined with MRI over 4 or 6 h, respectively. US was performed immediately after MRI in right lateral decubital (RLD) and supine with upper body elevated (SUBE) positions. Correlation coefficients (Pearson R; 95%CI) between CSA and body weight corrected GCV (GCVw ) as determined by MRI volumetry were calculated. Data are presented as median (range). Results: Eighteen children aged 9.8 (6.8–12.2) years had 72 US examinations completed. CSA was 401 (101–1311) mm 2 and 271 (118–582) mm 2, and R between CSA and GCVw was 0.76 (0.76–1) and 0.57 (0.41–0.88) for the RLD and SUBE positions, respectively. The corresponding GCVw was 2.1 (0.1–13.8) ml·kg −1 . A linear regression model from RLD was similar to one previously derived. Bland–Altman analysis and ROC plots are presented. Conclusion: CSA correlated with GCVw in healthy children over a wide range of gastric filling, with the RLD position clearly superior to the SUBE position, confirming a previously derived formula. Although direct calculation of GCVw is imprecise, this technique has the potential to become a diagnostic risk assessment test. Abstract :